Dampak Penggunaan E-Modul IPA Terintegrasi STEM untuk Penguatan Sustainable Development Goals (SDGs) dan Profil Pelajar Pancasila Dimensi Berpikir Kritis: Literatur Review - Muh. Arafatir Al Jarwi; Kosim; Joni Rohkmat; A. Wahab Jufri (Kappa Journal, 2024)
This study aimed to determine the impact of using STEM-integrated Science E-modules to strengthen the Sustainable Development Goals (SDGs) and the profile of Pancasila students in the critical thinking dimension. The method used is a systematic literature review (SLR) approach to identify, disseminate, and synthesize relevant evidence on the impact of STEM integration in e-modules to strengthen the Sustainable Development Goals (SDGs) and Pancasila students' professional critical thinking dimensions. E-modules with a STEM approach have developed rapidly in recent years. This study provides a significant impact and potential for improving the quality of science learning and learning materials for students. Several studies have shown the effectiveness of STEM-based E-modules in enhancing students' critical thinking skills. Previous studies have revealed that the STEM approach can improve students' critical thinking skills.